F- and F+-band radioluminescence and the influence of annealing on its emission spectra in Al2O3:C, Mg. (June 2020) - Chithambo, M.L.; Kalita, J.M.; Finch, A.A.
Abstract: Radioluminescence spectra of Al2 O3 :C, Mg monitored at temperatures up to 400 °C is reported. Measurements were made on samples either as received or on ones annealed at 1200 °C. Radioluminescence is observed at 410 nm for the unannealed sample but principally at 330 and 410 nm in the annealed sample with the emission at 330 nm dominant. Both bands are subject to thermal quenching but the change for the F + band is atypical. Temperature induced effects on these and other bands are discussed, as are complementary measurements of thermoluminescence spectra. Highlights: Radioluminescence from α-Al2 O3 :C, Mg is reported. The signal includes bands at 330, 410, 510, 700 and 750 nm. The 330 nm is more prominent in annealed samples. Both the 330 and 410 nm bands are affected by thermal quenching.